(untitled) (Eurasian Journal of Ecology, 2025)
This article considers the main problems contributing East Zangezur, a region of strategic and ecological significance in Azerbaijan, has emerged as a focus of large-scale restoration efforts following its liberation. Comprising Jabrayil, Kalbajar, Lachin, Gubadli, and Zangilan districts, the district boasts diverse natural resources, including forests, rivers, and fertile soils. Despite the damage inflicted during the occupation, substantial progress is being made to restore the ecological balance, including forest regeneration, water purification, and renewable energy initiatives. This study emphasizes the solar energy potential of Zangilan, Kalbajar, and Gubadli districts, highlighting their geographical advantages and year-round sunlight availability. Detailed calculations of solar radiation and zenith angles on March 20th 2024 demonstrate the viability of solar projects in these areas. The findings underscore East Zangezur’s renewable energy prospects and its role in Azerbaijan’s sustainable development strategy. Keywords: East Zangezur, sustainable development, renewable energy, solar energy potential, solar panel installations